2021
DOI: 10.3390/cimb43020079
|View full text |Cite
|
Sign up to set email alerts
|

Saussurea lappa Exhibits Anti-Oncogenic Effect in Hepatocellular Carcinoma, HepG2 Cancer Cell Line by Bcl-2 Mediated Apoptotic Pathway and Mitochondrial Cytochrome C Release

Abstract: Background and Objectives: Saussurea lappa (S. lappa) is an important species of the Asteraceae family with several purposes in traditional medicine. This study intended to explore the cytotoxic effect of S. lappa on HepG2 cancer cell proliferation. Materials and Methods: The effects of an S. lappa n-butanol extract on the induction of apoptosis were investigated by flow cytometry and mitochondrial cytochrome C-releasing apoptosis assay. Additionally, real-time PCR was employed to confirm apoptosis initiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…The pellet was collected and washed with PBS. Then, 5 µL of Fluorescein Isothiocyanate-Annexin V (FITC-Annexin V) was mixed with the pellet with a gently vortexed motion and incubated at 25 °C for 15 min in the dark, followed by the addition of 5 µL of Propidium Iodide (PI) and 400 µL of 1X binding buffer and analyzed by flow cytometry [ 50 , 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pellet was collected and washed with PBS. Then, 5 µL of Fluorescein Isothiocyanate-Annexin V (FITC-Annexin V) was mixed with the pellet with a gently vortexed motion and incubated at 25 °C for 15 min in the dark, followed by the addition of 5 µL of Propidium Iodide (PI) and 400 µL of 1X binding buffer and analyzed by flow cytometry [ 50 , 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…The plates were covered with aluminum foil to avoid exposure to the light and incubated for 4 h. A total of 100 µL dimethyl sulfoxide (DMSO) (#PHR1309, Sigma Aldrich, Bangalore, India) solubilization solution was added to each well to dissolve the formazan format on the last step. The absorbance was recorded at 570 nm by the ELISA reader, and the IC 50 value was calculated by using a linear regression equation, i.e., Y = Mx + C, where Y = 50, M, and C values were derived from the viability graph [31,32]. Three independent experiments were performed.…”
Section: Anticancer Activity Of Synthesized P-agnps From P Alba Leaf Extractmentioning
confidence: 99%
“…Our findings indicated that the targeted genes of PMS against myocardial hypoxia-reoxygenation injury are involved in ILK and mitochondrial apoptosis signaling pathways, including ILK, c-Src, Akt, Cytochrome c and caspase-3. H/R stimulation in cardiomyocytes decreased the expression of ILK [18], which can result in the phosphorylation of c-Src and inhibit the expression of Akt, which induces a series of signal transduction pathways to ultimately regulate Bcl-2 and Bax, thereby leading to release of cytochrome c and increasing the expression of caspase-3 [40][41][42]. Our present western blot results showed the expression of ILK, p-Akt and Bcl-2 decrease, and the expression of p-c-Src, Bax, cytochrome c and caspase-3 increase after H/R treatment, which is in consistency with the previous report.…”
Section: Discussionmentioning
confidence: 99%